Integrating Artificial Intelligence and Ethnopedagogy in ESD: A Conceptual Model for Social Studies Learning and National Resilience - Ahmad Imam Khairi; Sugiantoro Sugiantoro; Itaanis Tianah; A. Fatikhul Amin Abdullah; Muhammad Hadiatur Rahman; Salman Al Farisi (IAIN Madura, 2026)
Education for Sustainable Development (ESD) has become increasingly important in addressing complex global challenges affecting national resilience, including environmental crises, technological disruption, and social transformation. However, its implementation in social studies learning remains limited, particularly in integrating advanced technology with local wisdom values. This study aims to conceptually examine the strengthening of ESD through the integration of artificial intelligence within an ethnopedagogical approach in social studies education. The research employs a literature review method with an analytical-critical approach, drawing on relevant and reputable scientific sources published over the past decade. The findings indicate that artificial intelligence enhances learning through improved accessibility, personalization, and data-driven instruction, while ethnopedagogy reinforces contextual relevance by embedding local cultural values. The integration of these dimensions within the ESD framework offers a comprehensive learning model that is adaptive, contextual, and oriented toward developing students’ critical awareness of sustainability issues. This study highlights the importance of constructing an integrative conceptual framework that combines technology and local wisdom as a strategic approach to strengthening sustainable national resilience.